Visual pollution resulting from the indiscriminate use of the colors of the external facades - Western Corniche in the city of Latakia - محمد , رزان; أسعد علي ,; ريم المعلم , (Latakia University Journal -Engineering Sciences Series, 2023)
Each city has an image that distinguishes it from the rest of the cities, which is entrenched in the mind of the recipient and leaves in himself a mixture of feelings and memories , They differ according to the aesthetic design and the consistency of the visual components of the image, And the proper architectural and urban formation of the city with all its material and technical elements. In most of our cities, in recent times, manifestations of visual pollution have clearly spread, Sometimes as a result of poor design, planning and implementation, And the wrong use of the manifestations of development and the elements of modern technology in architecture at other times, With the lack of continuous follow-up and control to contain and control this problem. This research will monitor the phenomenon of visual pollution in the city of Lattakia as it is the bride of the coast and must enjoy the appearances of beautiful, harmonious architecture, The focus will be on the manifestations resulting from the random use of colors in the exterior facades of the western cornice buildings as a study sample. Within the framework of analyzing these phenomena, identifying their causes and proposing appropriate solutions